2018
DOI: 10.7717/peerj.4923
|View full text |Cite
|
Sign up to set email alerts
|

Sex-based differences in anti-predator response of crickets to chemical cues of a mammalian predator

Abstract: Anti-predator behaviors like vigilance or hiding come at the expense of other fitness increasing behaviors such as foraging. To compensate for this trade-off, prey assess predation risk and modify the frequency of anti-predator behaviors according to the likelihood of the threat. In this study, we tested the ability of house crickets (Acheta domesticus) to indirectly assess predation risk via odors from a mammalian predator, Elliot’s short-tailed shrew (Blarina hylophaga). As natural differences in encounter r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
8
1
Order By: Relevance
“…Contrary to much of the literature (Monclús et al 2005;Zidar & Løvlie 2012;Zöttl et al 2013;Kuijper et al 2014;Garvey et al 2016;Kern et al 2017;Tanis et al 2018), we found no change in sentinel rate following a SPC encounter. It is nevertheless possible that there may have been changes in other vigilance types such as quadrupedal vigilance (scanning on four legs) as reported in Zöttl et al ( 2013), which were not recorded in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to much of the literature (Monclús et al 2005;Zidar & Løvlie 2012;Zöttl et al 2013;Kuijper et al 2014;Garvey et al 2016;Kern et al 2017;Tanis et al 2018), we found no change in sentinel rate following a SPC encounter. It is nevertheless possible that there may have been changes in other vigilance types such as quadrupedal vigilance (scanning on four legs) as reported in Zöttl et al ( 2013), which were not recorded in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…The most common responses are cue avoidance (of either the cue itself (Caine & Weldon 1989) and/or the area the cue was encountered (Grostal & Dicke 1999;Sike & Rózsa 2006;Amo et al 2011;Weiss et al 2015)) and increased vigilance (e.g. Monclús et al 2005;Zöttl et al 2013;Garvey et al 2016;Tanis et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These cues can indicate predator presence in the vicinity and provide information about the nature of the threat. In most cases prey avoid SPCs or respond with defensive behaviours such as increased vigilance (Monclús et al 2005;Zidar & Løvlie 2012;Garvey et al 2016;Tanis et al 2018), reduced activity (Persons et al 2001;Sullivan et al 2002;Lehtiniemi 2005), refuge use (McGregor et al 2002;Sullivan et al 2002;Ferrari et al 2006;Belton et al 2007), and moving away from the cue (Amo et al 2004;Shrader et al 2008;Mella et al 2014). However, some species respond by approaching and inspecting SPCs, presumably to gain further information about the source of the cue (Belton et al 2007;Furrer & Manser 2009;Zöttl et al 2013;Garvey et al 2016;Collier et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…males may show more exploratory behaviors) or perhaps female crickets are more capable of detecting predator signals and consequently reducing their activity. For instance, A. domesticus females delay their foraging in the presence of a mammal predator odor [26]. Another potential chemical cue that may have influenced our results is that scorpions were fed with A. domesticus before the experiments and there is evidence that A. domesticus avoid chemical cues produced by predators fed on A. domesticus, as compared to the same predators fed on other insects [27].…”
Section: Discussionmentioning
confidence: 93%
“…Perhaps this weakened any potential luring by the fluorescence. Overall, it seems that predator avoidance in house crickets depends on chemical cues [26][27][28]. Whether scorpions emit a chemical signal detectable (e.g.…”
Section: Discussionmentioning
confidence: 99%